Factors affecting nutrient concentration and stoichiometry of forest trees in Catalonia (NE Spain) - Sardans, J.; Rivas-Ubach, A.; Penuelas, J. (Forest Ecology and Management, 2011)
Although some studies have observed signiﬁcant correlations between latitude and climate gradients and tree leaf nutrient concentration and stoichiometry, others have not. This study examined the nutrient concentrations of tree leaves in 3530 plots of the Catalonian Forest Inventory. Catalonia is a Mediterranean region located in NE Iberian Peninsula. It has a long land-use history and includes the large industrial-urban area of Barcelona but still contains a large forest area (42%). In the forests of Catalonia, leaf nutrient concentration increased and leaf C:nutrient ratios decreased from south to north, which paralleled the increase in MAP (mean annual precipitation) and the decrease in MAT (mean annual temperature), which was expected in a Mediterranean climate where the availability of water is the most limiting factor for plant nutrient uptake. In addition, the availability of water, which inﬂuences productivity, was associated with low leaf N:P content ratios, which is consistent with the Growth Rate Hypothesis. At a regional scale, the results support the Soil-Age Hypothesis because the youngest soils in the Pyrenees had the lowest leaf N:P ratios. Furthermore, the type of forest (evergreen, deciduous, or coniferous) explained some of the variation in leaf nutrient concentrations and stoichiometry. Nutrient concentrations were highest in deciduous trees and lowest in coniferous trees. Leaf nutrient concentrations and stoichiometry were mainly correlated with climate, but other factors such as the chemical properties of soil and rock, phylogenetics, and different ecological histories and anthropogenic factors such as pollution, had an effect.
The following values have no corresponding Zotero field: publisher: Elsevier B.V.
Keywords: ecological stoichiometry; forest climate influence; mediterranean forest; Tree nutrient relationships